2013
DOI: 10.1308/003588413x13629960045995
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of weight loss achieved after laparoscopic adjustable gastric banding between Afro-Caribbean, Caucasian and South Asian adult female patients in a London bariatric centre

Abstract: Introduction It has been shown that following laparoscopic adjustable gastric banding (LAGB) procedures, Afro-Caribbeans achieve poorer weight loss compared with Caucasians. The reasons for this are multifactorial. However, studies have been based on mainly female patients from the US and none to date have been from the UK. Furthermore, South Asians have not previously been compared. The aim of this study was to compare excess weight loss percentage (%EWL) outcomes up to five years following LAGB in Afro-Carib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…A number of studies report greater weight loss for Caucasian than for African American patients [12,13,[17][18][19][21][22][23], but some have not [20,[24][25][26][27][28] and 1 has found the opposite pattern in men [28]. Earlier studies finding differences in weight loss outcomes focused mainly on either RYGB [12,[17][18][19][20]27,28] or LAGB [11,[23][24][25]. Only Araia et al [26] assessed gastric sleeve, gastric banding, and RYGB, finding no difference in BMI at 1-year follow-up between African American and Caucasian patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies report greater weight loss for Caucasian than for African American patients [12,13,[17][18][19][21][22][23], but some have not [20,[24][25][26][27][28] and 1 has found the opposite pattern in men [28]. Earlier studies finding differences in weight loss outcomes focused mainly on either RYGB [12,[17][18][19][20]27,28] or LAGB [11,[23][24][25]. Only Araia et al [26] assessed gastric sleeve, gastric banding, and RYGB, finding no difference in BMI at 1-year follow-up between African American and Caucasian patients.…”
Section: Discussionmentioning
confidence: 99%
“…Diet and exercise interventions show slightly greater weight loss in Caucasians compared to African American patients [14][15][16] and extant bariatric studies report mixed results regarding ethnic differences in surgical weight loss outcomes. Some studies have found greater weight loss in Caucasian versus African American patients [12,13,[17][18][19][20][21][22][23] and others have not [20,[24][25][26][27]. In fact, 1 study has found that African American men achieve greater weight loss than Caucasian men [28].…”
mentioning
confidence: 99%